Extracellular matrix proteins as temporary coating for thin-film neural implants. (9th January 2017) - Ceyssens, Frederik; Deprez, Marjolijn; Turner, Neill; Kil, Dries; van Kuyck, Kris; Welkenhuysen, Marleen; Nuttin, Bart; Badylak, Stephen; Puers, Robert
Abstract: Objective . This study investigates the suitability of a thin sheet of extracellular matrix (ECM) proteins as a resorbable coating for temporarily reinforcing fragile or ultra-low stiffness thin-film neural implants to be placed on the brain, i.e. microelectrocorticographic ( µ ECOG) implants. Approach . Thin-film polyimide-based electrode arrays were fabricated using lithographic methods. ECM was harvested from porcine tissue by a decellularization method and coated around the arrays. Mechanical tests and an in vivo experiment on rats were conducted, followed by a histological tissue study combined with a statistical equivalence test (confidence interval approach, 0.05 significance level) to compare the test group with an uncoated control group. Main results . After 3 months, no significant damage was found based on GFAP and NeuN staining of the relevant brain areas. Significance . The study shows that ECM sheets are a suitable temporary coating for thin µ ECOG neural implants.